The teaching content of Shanghai style furniture design for Chinese art design speciality. Issue 11 (November 2022) - Zou, Weihua; Li, Zimu; Sun, Delin
Abstract: Shanghai style furniture (SSF) was the classic case of Chinese furniture culture, we have researched on the teaching content of SSF design for the furniture design course in Chinese art design speciality, and carried out the teaching practice of SSF design for some students. According to this teaching practice, the students' design attitude towards SSF was summarized, which will provide a basis for inheriting SSF design and developing SSF design teaching. In our teaching practice, 132 students had learned the design experiences of SSF, carried on the design practice of SSF, and summarized their SSF design. In the process of students' redesign of SSF, generally speaking, the SSF style was characterized by the combination of China and the European and modern simplicity. Modern elements were added to the SSF design, and fine works were refined in the traditional Chinese modeling, so as to make SSF more in line with the trend of modern design and better carry forward the concept of design service life. After studying this course, these students had basically mastered the design method of SSF. Excavating the practical value of SSF culture and designing new SSF, which are not to copy traditional art style, but the recreation and redesign basing on modern cultures. Abstract : Shanghai style furniture (SSF); Chinese art design speciality; Redesign; Simplified elements; Reformed forms.